The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/pcan.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the TEP1 gene are associated with prostate cancer risk and recurrence

Abstract: BACKGROUND:Telomere-related genes play an important role in carcinogenesis and progression of prostate cancer (PCa). It is not fully understood whether genetic variations in telomere-related genes are associated with development and progression in PCa patients. METHODS: Six potentially functional single-nucleotide polymorphisms (SNPs) of three key telomere-related genes were evaluated in 1015 PCa cases and 1052 cancer-free controls, to test their associations with risk of PCa. Among 426 PCa patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…It should be noted that genetic variants that affect telomere length, telomerase activation, and telomeric protein configuration may cause functional changes responsible for cancer development and further tumor growth. Cancer Genome Association Studies have shown that single-nucleotide polymorphisms (SNPs) in telomere-associated genes are associated with a risk of developing various tumors [ 20 ]. In the literature on the selected polymorphisms, only a possible association with tumors of other localizations has been described [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that genetic variants that affect telomere length, telomerase activation, and telomeric protein configuration may cause functional changes responsible for cancer development and further tumor growth. Cancer Genome Association Studies have shown that single-nucleotide polymorphisms (SNPs) in telomere-associated genes are associated with a risk of developing various tumors [ 20 ]. In the literature on the selected polymorphisms, only a possible association with tumors of other localizations has been described [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…TEP1 (telomerase‐associated protein 1, 14q11.2) gene product is a component of the telomerase enzyme complex . TEP1 SNPs have been associated with the risks of bladder , stomach , prostate , and breast cancer , the prognosis of liver and prostate cancer , and the risk of type 2 diabetes . Although TEP1 is a telomerase‐binding protein, previously it was shown that TEP1 is not essential for telomerase activity or telomere length maintenance in a mouse model .…”
Section: Discussionmentioning
confidence: 99%
“…Irregular function of this protein resulting from unbalanced gene expression or genetic variation may affect genome and chromosomal stability and promote cancer development. Previous findings of TEP1 polymorphisms were reported in many cancers such as prostate cancer (Gu et al, 2015), breast cancer (Varadi et al, 2009) and bladder cancer (Chang et al, 2012) as well as in male infertility (Yan et al, 2014). Recent study in Korea cohorts demonstrated that TEP1 polymorphisms were associated with risk of HCC, especially in rs1713449 by using high-throughput SNPs genotyping assay (Jung et al, 2014).…”
Section: Association Of Pinx1 But Not Tep1 Polymorphisms With Progression To Hepatocellular Carcinoma In Thai Patients With Chronic Hepatmentioning
confidence: 93%